Immobilization and growth effects on viscoelastic properties of soft tissues : application to rabbit patellar tendons - Tan, Soon Huat. (2010)
Response of tendons and ligaments to the change of mechanical environment, i.e., remodelling, is a great concern of biomechanical and orthopedic research. Due to sports and traffic accidents, the incidence of injuries in the lower extremity is increasing. Surgical treatments are often required to repair these injuries. During and after surgery, the knee joint must be immobilized for a period of time, and because of the immobilization, load and stress applied to the knee joint are greatly reduced. In view of this, it is crucial to know the effects of stress deprivation on the structural, mechanical and viscoelastic properties of tendons and ligaments. Previous studies have shown that the reaction of the patellar tendon due to immobilization of a knee is greater and occurs earlier in immature rabbits than in mature ones. The tensile strength and modulus of the patellar tendons are markedly decreased by immobilization. In addition, a long period is required for recovery from a relatively brief period of immobilization. At present, the effect of knee immobilization on viscoelastic properties, such as strain rate dependence and stress relaxation, of the patellar tendons has not been thoroughly investigated. Therefore, the objective of this study is to quantitatively determine the effect of knee immobilization on viscoelastic properties of the rabbit patellar tendons, and compare the immature rabbits with the mature ones.